A concept analysis of theory in South African Open Distance and E-Learning research. (4th May 2021) - Zongozzi, J.N.
ABSTRACT: A conceptual confusion of theory exists in South African Open Distance and e-Learning (ODeL) research in which the concept is used with borderline, related, contrary, invented, or illegitimate concepts such as a model, approach, construct, hypothesis, theoretical framework, or conceptual framework. As a result, some researchers choose not to apply theory, apply a narrow definition, or risk their manuscripts being rejected when theory is inadequately applied. This article seeks to expand the understanding of the concept theory in South African ODeL research. In particular, the purpose of the paper is to clarify the meaning and reduce ambiguities surrounding theory, as well as promote consistency in using the concept in South African ODeL research. Subsequently, the article develops a conceptual framework through a comprehensive literature review, and through the application of the eight steps for a concept analysis. This framework consists of six conceptual components related to the application of theory in order to meet the expected outcome of a particular ODeL research project. Four of the components that are deemed more important include defining attributes, identifying model cases, antecedents, consequences and empirical referents. The conceptual framework serves as a thinking tool for an integrated and deepened understanding of the concept theory and for enhancing the appropriate use of theories in South African ODeL research.